2019
DOI: 10.5817/cp2019-1-2
|View full text |Cite
|
Sign up to set email alerts
|

Social comparison orientation mediates the relationship between neuroticism and passive Facebook use

Abstract: Passive Facebook use, which involves engaging in non-socially orientated behavior on the popular social networking site, is associated with a range of negative outcomes, including social anxiety, loneliness, jealousy, and depressed mood. Research indicates that passive Facebook use may also be related to a tendency to engage in social comparison with others. In addition, there is some evidence that this tendency is more prevalent in individuals high in the personality trait neuroticism. The aim of this study w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 93 publications
(142 reference statements)
1
41
0
Order By: Relevance
“…This would mean that instead of actively communicating with other users on Instagram, these individuals could be browsing the content, posts, and profiles of other users. There is some evidence for that in Facebook use research, where it has been shown that passive Facebook use (lurking) is associated with factors relevant to psychopathology, such as more social comparison and neuroticism, and lower levels of psychological well-being (Gerson et al, 2017; Rozgonjuk, Ryan, Kuljus, Täht, & Scott, 2019; Verduyn et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…This would mean that instead of actively communicating with other users on Instagram, these individuals could be browsing the content, posts, and profiles of other users. There is some evidence for that in Facebook use research, where it has been shown that passive Facebook use (lurking) is associated with factors relevant to psychopathology, such as more social comparison and neuroticism, and lower levels of psychological well-being (Gerson et al, 2017; Rozgonjuk, Ryan, Kuljus, Täht, & Scott, 2019; Verduyn et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Individuals have a tendency to overestimate the positive experiences and underestimate the negative emotional experiences of people they are following on SNS (Jordan et al., 2011; Rozgonjuk et al., 2019). This results in followers seeing a positively skewed version of other people’s lives (Reagle, 2015) and therefore believing these people to be happier, more successful, and more emotionally positive than themselves (Chou & Edge, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Individuals who are high in neuroticism are excitable, easily upset, and prone to experiences that are unpleasant [50]. They are also more sensitive to criticism; they experience higher levels of rejection; and they have lower self-esteem [51]. In prior research, neuroticism has been connected to the increased drive for thinness in women [52,53], to heightened food and body preoccupation [54], to body dissatisfaction [55], to the self-regulation of eating attitudes (e.g., food temptation) [56], and even to eating disorder diagnosis [48,57] and binge eating [58,59].…”
Section: Neuroticismmentioning
confidence: 99%